전통마을 방문객 만족요인이 전반적 만족도와 행동의도에 미치는 영향 -아산 외암 마을을 대상으로 - 이종주; Lee, Jong-Joo (한국콘텐츠학회 논문지, 13(3), 2013)
A traditional house or a traditional village experience has been on the rise as a form of experiential cultural tourism. But the Oeam folk village, a experiential cultural tourist destination representing Chungcheng-do seems to confront the stagnancy in the part of growth. It has to grow in two sides of quantity and quality. On the ground of this critical mind, 3 assumptions were established after analyzing previous studies. Additionally, market segmentation using satisfaction factors was practiced. In order to verify assumptions, A questionnaire was made and a survey was practiced. Out of statistic analyses, cluster analysis was practiced to do market segmentation targeting people who visit Oeam folk village and regression analysis to verify established assumptions. The assumption 1 was adopted that satisfaction factors influence whole satisfaction. The assumption 2 was partly adopted that satisfaction factors(sightseeing efficiency, sightseeing convenience, traditional house and experience factor) except food and souvenir factor influence behavior intention. The assumption 3 was adopted that whole satisfaction influences behavior intention. These were similar with the results of previous studies. As the result of cluster analysis to confirm the difference of demographic characteristics according to the market, 2 clusters was classified and classified clusters showed the difference of demographic characteristics. 전통 가옥이나 마을 체험은 하드웨어와 소프트웨어가 양립하는 매우 포괄적인 문화상품으로 급속한 성장을 하고 있으나 충청도를 대표하는 전통 체험형 관광지인 아산 외암 마을은 성장이 정체되어 있는 듯하다. 외암 마을은 양적인 성장과 더불어 질적 성장을 추진해야 하는 상황이다. 이런 문제의식을 가지고 선행연구를 바탕으로 가설을 설정하였다. 연구 분석을 위해 설문을 실시하였고, 수집된 설문을 가지고 SPSS 20.0을 이용하여 군집분석을 실시하였고 가설검증을 위해서 회귀분석을 실시하였다. 설정된 3개의 가설 중 가설 1은 만족요인이 전반적 만족도에 영향을 미침을 확인하였고, 가설 2의 경우 만족요인(음식 및 기념품, 관람효율성, 관람편의성, 전통가옥, 체험) 중 음식 및 기념품 요인이 행동의도(추천의도, 구전, 재방문)요인 중 재방문에 영향을 미치지 않음을 제외하고 만족요인은 행동의도에 영향을 미쳤다. 따라서 가설 2는 부분적으로 채택되었고, 가설 3은 전반적 만족도가 행동의도에 영향을 미쳤다. 설정된 모든 가설이 채택 되었다. 본 논문의 연구결과는 기존연구의 결과와 유사 하였다. 설정된 가설검증 이외에도 만족도 요인을 이용한 군집분석을 통하여 관광객 시장을 2개로 분류하였고 분류된 시장에 따라 인구통계적 특성의 차이가 있음을 확인하였다.